(untitled) (Orinoquia, 2022)
Scientific research may be seen as a complex and complicated process; however, it is considered a fundamental pillar for improving the quality of life, social welfare, training graduates and future researchers’ development (Delgado-Bardales, 2021). Scientific research undoubtedly brings great social benefits with it, although it is not given the importance that it deserves in many developing countries. For example, few economic resources are allocated by Latin American countries for this activity, i.e. less than a fifth of that allocated (of GDP) by developed countries. Scientific research is largely based on researchers’ collaboration and cooperation, whether this concerns research groups from the same institution, research networks from different institutions in the same country or international networks. It is thus clear that international scientific cooperation (ISC) has enabled and promoted science’s modernisation in Latin America. Transferring financial resources by providing subsidies for science and research can be highlighted as one of the ISC’s main mechanisms. International government agencies, societies and philanthropic associations in Europe and the United States prioritised allocating economic resources and promoted networks for carrying out scientific affairs during the first half of the 20th century (Estébanez, 2019). Advances regarding the modernisation of science in this region have been achieved through strategies aimed at supporting recognised researchers and emerging scientific groups, as well as creating research institutions and providing support for scientific education. It can be seen that Latin American countries have managed to maintain strategies for advancing and modernising scientific activity, despite the fact that the percentage of GDP allocated for such purposes is low (compared to developed countries). It can be said that many Latin American countries specifically invest part of their economic resources in carrying out international scientific activities by providing government subsidies and financing research institutions and/or non-governmental organisations (NGOs). Investing in ISC has resulted in great social benefits for the region and it is clear that this has enabled/enhanced greater visibility for scientific research at international level. Latin American countries do not allocate more than 0.6% to 0.7% of GDP for research activities, even though science, technology and innovation are the most relevant issues worldwide; this can be compared to countries considered developed, such as China, the United Kingdom and the United States, investing an average 4% of their GDP in research (Infobae, 2021 (Argentinian online newspaper)). The best way to ensure greater certainty regarding the investment of economic resources, and thereby the modernisation of science, is through the enactment of public policy in the states/departments, as is currently happening in various countries, such as Colombia, Mexico, Argentina, Brazil. Some of the main international strategies being followed are researcher mobility, research network formation, student mobility and training human resources in the field of scientific research.